2019
DOI: 10.1002/jobm.201900427
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial effect of TiO2:Cu:Ag thin coatings on Pseudomonas strain measured by microbiological and ATP assays

Abstract: The aim of this study is to investigate the antimicrobial properties of nanocomposite thin TiO2:Cu:Ag films on Pseudomonas putida as a natural isolate and an opportunistic pathogen. Several different methods were used to compare the antibacterial effect of thin TiO2:Cu:Ag layers obtained by radiofrequency magnetron sputter deposition against P. putida: optical density of the bacterial suspension, most probable number of survived cells, dehydrogenase activity inhibition, scanning electron microscopy images, ato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A study by Tyllianakis et al [84] has shown that the antibacterial effect of nanocrystalline TiO 2 /Ag increases with the decrease of its size. Similarly, Ivanova et al [52] have demonstrated that nanocomposite TiO 2 /Cu/Ag coatings have a strong antimicrobial effect and a high potential in medical applications.…”
Section: Tio 2 Npsmentioning
confidence: 90%
“…A study by Tyllianakis et al [84] has shown that the antibacterial effect of nanocrystalline TiO 2 /Ag increases with the decrease of its size. Similarly, Ivanova et al [52] have demonstrated that nanocomposite TiO 2 /Cu/Ag coatings have a strong antimicrobial effect and a high potential in medical applications.…”
Section: Tio 2 Npsmentioning
confidence: 90%
“…An enhanced antimicrobial effect was obtained with a combination of TiO 2 with CuO and two-layer structures of Ag and CuO in combination with TiO 2 . [57,[75][76][77]. Structures where Ag and CuO are inlaid on TiO 2 have higher biocidal activity.…”
Section: Copper Oxide's Biological Effectsmentioning
confidence: 99%
“…In the area of bacteria detection, the ATP luminescent method can be used to measure the amount of bacteria conveniently and quickly. In comparison with previous cell counting methods [ 22 ], this method has the advantages of simple operation and quick identification, and this method may have applications in clinical detection.…”
Section: Introductionmentioning
confidence: 99%